Pembelajaran STEM Berbasis Proyek Menggunakan Media Jembatan Berlampu - Erwani Merry Sartika; Markus Tanubrata; Olga Catherina Pattipawaej; Rainisa Maini Heryanto; Meilan Jimmy Hasugian; Novie Theresia Br. Pasaribu; Dido Hardinanto Ginting; Gibran Qodri Nurfalah; Muhamad Dani Ardiansyah (Jurnal Atma Inovasia, 2026)
This community service activity aimed to enhance elementary school students’ understanding of bridge structural concepts and simple electrical circuits through individual project-based STEM learning. The activity was conducted with Grade 3–4 students in the Cibogo area, utilizing simple materials such as popsicle sticks, LEDs, wires, batteries, and switches as learning media. The methodology integrated community-based research, participatory learning, and action research approaches, in which the activities were designed based on the needs of the target community, actively engaged students in the learning process, and incorporated reflective practices for continuous improvement. Evaluation was carried out using a questionnaire to assess students’ understanding of bridge structures, simple electrical circuits, and their responses to the activity. The evaluation results indicated that most students were able to comprehend the fundamental concepts introduced and showed positive responses to the project-based learning activities (85% for bridge construction and 78% for electrical circuits). In addition to improved conceptual understanding, students demonstrated high levels of interest and enthusiasm throughout the activity. It can be concluded that this activity was effective in providing meaningful and contextual learning experiences. Future implementations may be further developed by strengthening introductory materials and diversifying project models to enhance the quality and sustainability of STEM learning in elementary school environments.